Age Vs Awarness : A Cross-Sectional Insight Into Emesis Gravidarum Among Early Pregnancy - Diti Arianti; Nila Widya Keswara; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Emesis gravidarum (EG) is a common condition experienced by pregnant women, characterized by nausea and vomiting that can negatively impact the health of both the mother and the fetus. Although often considered a normal part of pregnancy, EG can significantly impact a mother's quality of life. Age factors are thought to have an effect on the level of maternal knowledge about this condition, with older mothers tending to have a better understanding than younger mothers. This study used a quantitative design with a cross-sectional approach. A sample of 30 pregnant women in the first trimester was taken using the purposive sampling technique. Data were collected using questionnaires and analyzed using Pearson correlation tests. 60% of respondents were multigravida, and 40% of respondents (100%) were between the ages of 20 and 35. Seventy percent of people throw up more than three times a day. With an average score of 73.40 (on a scale of 50 to 90), Mother's level of knowledge showed variances in comprehension. The normality test revealed that the knowledge and age data were normally distributed. Since there was no discernible association between the mother's age and her degree of knowledge (r = 0.139, p = 0.465) according to the Pearson correlation test, other variables like education and information availability might be more important factors influencing knowledge. The age of the first-trimester pregnant women and their level of EG knowledge did not significantly correlate. Consequently, comprehensive health education is essential to enhance pregnant women's comprehension of EG, irrespective of age considerations.